ANTI-TUBERCULAR ACTIVITY OF EDTA AND HOUSEHOLD CHEMICALS AGAINST MYCOBACTERIUM SMEGMATIS, A SURROGATE FOR MULTI-DRUG RESISTANT TUBERCULOSIS - Francis E. Umesiri; Ashley Lick; Christine Fricke; Joel Funk; Thomas Nathaniel (European Scientific Journal, ESJ, 2015)
Drug discovery efforts are increasingly being directed at re-purposing old drugs for use in treatment of multidrug resistant tuberculosis (MDRTB) which continues to pose serious health challenges worldwide. Recent studies suggest that Mycobacterium smegmatis, with innate resistance to isoniazid, could be used as a surrogate for MDRTB screening in laboratories without adequate containment facilities. The current study utilized resazurin microtiter assay plate (REMA) to screen common household chemicals and non-steroidal anti-inflammatory drugs (NSAIDs) for anti-tubercular activity against Mycobacterium smegmatis, as a non-pathogenic surrogate of MDRTB. A ligand-based approach was adopted in selecting household chemicals; using molecular docking tools to probe for binding affinity to Enoyl-[acyl-carrier-protein] reductase (InhA), the main target of isoniazid. Among household chemicals and analgesics studied, EDTA and lauric acid showed the highest activity with minimum inhibitory concentration (MIC) of 31 μg/mL and 7.8 μg/mL respectively, while Ibuprofen and aspirin exhibited activity with MIC of 125 μg/mL. Taken together, this study demonstrates the potential use of EDTA, lauric acid or NSAIDs in treatment of drug-resistant tuberculosis, a major contribution of the current study